2022
DOI: 10.1016/j.ijcard.2022.01.063
|View full text |Cite
|
Sign up to set email alerts
|

Renal decline in patients with non-valvular atrial fibrillation treated with rivaroxaban or warfarin: A population-based study from the United Kingdom

Abstract: Background: Reports suggest that renal decline is greater among patients with non-valvular atrial fibrillation (NVAF) treated chronically with warfarin vs. some non-vitamin K antagonist oral anticoagulants. Methods and results: Using primary care electronic health records from the United Kingdom we followed adults with NVAF and who started rivaroxaban (20 mg/day, N = 5338) or warfarin (N = 6314), excluding those with estimated glomerular filtration rate (eGFR) <50 ml/min/1.73m 2 , end-stage renal disease (ESRD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Data from systematic reviews and meta-analyses have shown that, in patients with moderate CKD (eGFR 30–59 mL/min) and AF or VTE, DOACs compared to warfarin have a superior or equivalent safety and efficacy profile [ 93 , 94 ]. Post-hoc analyses of phase 3 RCTs and observational data revealed that DOACs, in particular dabigatran and rivaroxaban, were associated with reduced loss of renal function compared to warfarin [ 90 , 95 ].…”
Section: Risk Of Bleeding Complications In Special Populationsmentioning
confidence: 99%
“…Data from systematic reviews and meta-analyses have shown that, in patients with moderate CKD (eGFR 30–59 mL/min) and AF or VTE, DOACs compared to warfarin have a superior or equivalent safety and efficacy profile [ 93 , 94 ]. Post-hoc analyses of phase 3 RCTs and observational data revealed that DOACs, in particular dabigatran and rivaroxaban, were associated with reduced loss of renal function compared to warfarin [ 90 , 95 ].…”
Section: Risk Of Bleeding Complications In Special Populationsmentioning
confidence: 99%
“…14,15 Although renal function decline is common among patients with AF, different studies have shown that compared with warfarin, rivaroxaban has a lower risk of renal function impairment. [32][33][34] In our study there was a modest reduction of renal function that could be explained by the high risk clinical profile (i.e., elderly patients with HF, AF, and many comorbidities). Although low diastolic blood pressure was associated with HF worsening, the worse clinical profile of these patients could explain at least in part this point.…”
Section: Discussionmentioning
confidence: 54%
“…Other studies found that rivaroxaban was associated with lower risks of a ≥30% decline in the eGFR, doubling of serum creatinine levels, and AKI than warfarin. 2,4,[6][7][8][9] When we stratified patients treated with the standard and off-label rivaroxaban doses to those treated with warfarin to compare their effects on renal function, we found that those treated with the off-label rivaroxaban dose had significantly higher risks of the composite of cardiac and renal events and a ≥30% decline in the eGFR than those treated with warfarin. This effect was not observed in patients treated with the standard rivaroxaban dose.…”
Section: T a B L E 1 (Continued)mentioning
confidence: 99%
“…Some studies have reported that dabigatran and rivaroxaban were associated with a lower risk of eGFR decline than warfarin. [4][5][6][7][8][9] A retrospective cohort study conducted in Taiwan showed that warfarin was associated with a significantly higher risk of AKI than DOACs. However, a comparison of dabigatran with other anti-factor Xa inhibitors indicated no difference.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation